Участь П.М. Добровольського в організації та проведенні XIV Всеросійського археологічного з’їзду у Чернігові - Матвієнко, Д.М. (Сіверщина в історії України, 2021)
Стаття присвячена XIV Археологічному з’їзду, що проходив у Чернігові за підтримки історика, краєзнавця, гласного Чернігівської міської думи П.М. Добровольського (1871–1910). На основі системного аналізу джерел та літератури розглянуто його внесок в організацію з’їзду, пошук фінансового забезпечення та систематизацію фондів. Було висвітлено етапи підготовки П.М. Добровольського до презентації археологічних, архівних та фольклорних матеріалів. Загальне уявлення про колекцію з’їзду складено на основі «Каталога выставки XIV Археологического съезда в г. Чернигове», складеного П.М. Добровольським. У статті розкрито практичну діяльність вченого як члена Чернігівської губернської вченої архівної комісії при підготовці до з’їзду на основі місцевих видань «Черниговское слово», «Черниговские губернские ведомости». The article is devoted to the XIV Archaeological Congress, which was held in Chernihiv with the support of the historian, local historian, vowel of the Chernihiv City Duma P. M. Dobrovolsky (1871–1910). At the present stage of development of Ukrainian Science, interest in the origins of Ukrainian history is growing. Based on a systematic analysis of sources and literature, his contribution to the organization of the Congress, the search for financial support and the systematization of funds are considered. The stages of preparation of P.M. Dobrovolsky for the presentation of archaeological, archival and folklore materials were highlighted. The general idea of the Congress collection is based on the «catalog of the exhibition of the XIV Archaeological Congress in Chernihiv» compiled by P.M. Dobrovolsky. The XIV Archaeological Congress was held in Chernihiv on August 1–12, 1908. Such prominent figures as Professor Samokvasov, historian Ilovaisky, director of the St. Petersburg Archaeological Institute Pokrovsky, professor Trutovsky and others were present. The article reveals the practical activity of the scientist as a member of the Chernihiv provincial scientific archival Commission in preparation for the Congress on the basis of local publications «Chernihiv provincial Vedomosti», «Chernihiv provincial Vedomosti». The study of biographies and scientific heritage of scientists of the XIX–XX centuries allows us to enrich Ukrainian historiography and restore historical memory. The paper reconstructs the process of Dobrovolsky’s formation as an authoritative scientist, identifies the factors that influenced the formation of his scientific views.